Evaluation of the workers exposure to heat and presenting intervention to control heat stress in profile factory - Motamedzade Majid; Eshaghi Mahbobeh; Sepehr Parvin (Muhandisī-i bihdāsht-i ḥirfah/ī, 2014)
Background & Objectives : Exposure to heat is a significant problem in the Industries. The present study aimed at the evaluation of thermal risk, measurement of heat stress index, and proposing a plan for heat control in cutting and welding units in profile factory .